2009
DOI: 10.1021/jf903080f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Synergistic Antioxidant Potential of Complex Mixtures Using Oxygen Radical Absorbance Capacity (ORAC) and Electron Paramagnetic Resonance (EPR)

Abstract: Previous research has demonstrated that certain combinations of compounds result in a decrease in toxic or pro-oxidative effects, previously noted when compounds were administered singly. Thus, there is a need to study many complex interactions further. Two in vitro techniques [electron paramagnetic resonance (EPR) and oxygen radical absorbance capacity (ORAC) assays] were used in this study to assess pro- and antioxidant capacity and synergistic potential of various compounds. Rutin, p-coumaric acid, abscisic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
1
34
1
2
Order By: Relevance
“…These findings are in agreement with our study that TAC assay and polyphenol composition both affect juice TAC interactions. A glucose, sucrose and fructose solution contributed to synergy between rutin and p‐ coumaric acid in the ORAC assay (Parker et al ., ), which conflicted with our finding that sugars and organic acids together interfered action of antioxidants in pomegranate‐nectarine and grape juices in TAC and total phenol assays. It is worth noting that we did not test the interaction using the sugar fraction alone in the study.…”
Section: Resultscontrasting
confidence: 83%
“…These findings are in agreement with our study that TAC assay and polyphenol composition both affect juice TAC interactions. A glucose, sucrose and fructose solution contributed to synergy between rutin and p‐ coumaric acid in the ORAC assay (Parker et al ., ), which conflicted with our finding that sugars and organic acids together interfered action of antioxidants in pomegranate‐nectarine and grape juices in TAC and total phenol assays. It is worth noting that we did not test the interaction using the sugar fraction alone in the study.…”
Section: Resultscontrasting
confidence: 83%
“…It is well known that members of the same group of polyphenols (phenolic acids, flavonols, flavone, etc.) do not have similar antioxidant activity despite having certain molecular similarity as this activity is a result of the environment and the presence of other compounds (Parker, Miller, Myers, Miguez, & Engeseth, 2010;Tabart, Kevers, Pincemail, Defraigne, & Dommes, 2009). It is likely that even though both extracts have similarities in composition, they do not have the same antioxidant capacity potentially due to the presence of unidentified compounds that could increase or have no effect on the antioxidant or antimicrobial activity observed in the extracts.…”
Section: Composition and Antioxidant Capacitymentioning
confidence: 99%
“…2, No. 6;Parker et al (2010 reported that more complex combinations of antioxidants tended to show more synergy when measured by the ORAC assay. Our results in this study partially agreed with this.…”
Section: Orac Synergy At the Chemical Levelmentioning
confidence: 99%
“…The combination of acerola cherry extracts and alfalfa and soy phytoestrogen extracts worked to inhibit LDL oxidation synergistically in vitro (Hwang et al, 2001). Parker et al (2010) found synergistic interactions between mixtures of rutin, p-coumaric acid, abscisic acid, ascorbic acid, and a sugar mixture using oxygen radical absorbance capacity (ORAC) and electron paramagnetic resonance (EPR). Hidalgo et al (2010) discussed synergy between mixtures of two phenolic compounds, finding synergy in many of the combinations.…”
Section: Introductionmentioning
confidence: 99%